Comparison of the Chinese Teacher Education System in China and Malaya (1945–1961) - Li, An (Advances in Humanities and Contemporary Studies, 2025)
This paper uses a comparative research method to examine the institutional evolution and practical characteristics of Chinese teacher education in China and Malaya during the period from 1945 to 1961. The study found that: Chinese teacher education in China showed the characteristics of state-led and serving socialist construction, and experienced four stages: post-war recovery, socialist transformation, learning from the Soviet model, and adjustment after the Great Leap Forward; while Chinese teacher education in Malaya developed in the tension between colonial control and the autonomous demands of the Chinese community, and experienced three stages: post-war colonial adjustment, independent transition, and establishment of a unit education system. The two places show significant differences in school system, curriculum structure, and social function: China has formed a hierarchical teacher college system and a dual-track training model for pre-service and post-service, emphasizing the unity of political education and professional knowledge; Malaya has gradually transitioned to a formal teacher college through short-term training courses, focusing on multilingual ability training and cultural identity coordination. The study reveals how the education system serves the dual goals of national construction and cultural inheritance in different political environments, and provides a historical mirror for understanding the development of teacher education in a multicultural context.